Conference of the Association of Inspectors of Education of the Basque Country: Inclusion. Definition and challenges for teachers and Educational Inspection - Totoricagüena Barandica, Karmele (Avances en Supervisión Educativa, 2017)
Last November 17, 2017, the training workshop "INCLUSION, DEFINITION AND CHALLENGES FOR THE TEACHER AND INSPECTION EDUCATIONAL " organized by the Association of Education Inspectors of the Basque Country (AIEE) was held at the Miguel Unamuno Institute in Bilbao.